Changes in Selected Quality Characteristics of Minimally Processed Carambola (Averrhoa Carambola L.) When Treated with Ascorbic Acid. - Ding, Phebe; Ahmad, Siti Hajar; Mohd Ghazali, Hasanah (2007)
Abstract: ‘ B 10’ carambola of ripening stages (RS) 3 and 4 were minimally processed (MP) and then dipped in 0, 15 and 30mg L -1 ascorbic acid (AA). The 1-cm-thick slices were then dried, packed into cling-wrapped-foam tray and stored at 7oC for 0, 3 and 5 days. Skin colour (L *, C* and ho), flesh firmness, soluble solids concentration, vitamin C content, titratable acidity, pH, degree of browning, polyhenoloxidase (PPO) activity and sensory attributes of MP carambola treated with AA were determined. AA treatment had significant effect in decreasing cut surface browning degree but no significant effect on all the selected quality characteristics of the MP carambola. In the sensory evaluation, flesh colour, sweetness, flavour and overall taste were significantly affected by AA treatment especially at 15mg L- 1. the RS of fruit significantly affected skin colour ( C* and ho ), pH and sensory attributes of colour and flavour ao the MP carambola. As storage day (SD) progressed, skin colour ( C* and ho ), flesh firmness and vitamin C content, cut surface browning, PPO activity and all the sensory attributes of MP carambola MP carambola positively correclated to each other but negatively correlated with browning degree. PPO activity positively correlated with browning degree.